PENGARUH BLANCHING BUAH KELAPA SAWIT TERHADAP KADAR ASAM LEMAK BEBAS (ALB) DAN DETERIORATION OF BLEACHABILITY INDEX (DOBI) MINYAK KELAPA SAWIT - Purwanto, Heri; Priadi, Ery (Jurnal Agro Fabrica, 2025)
Blanching at initial process can be done at the beginning before the process so that it will maintain the quality. Blanching is done to inactivate the endogenous lipase enzyme so that the rate of formation of free fatty acids and volatile compounds from the oil is inhibited. Blanching treatment affects Free Fatty Acids (FFA) and Deterioration Of Bleachability Index (DOBI). This process is a preliminary treatment before the fruit is processed in the factory. This study aims to determine the effect of blanching treatment on fruit bunches to maintain CPO quality from increasing Free Fatty Acids (FFA) and maintaining the Deterioration Of Bleachability Index (DOBI) value. This research was conducted in the PTPN IV laboratory, MAYANG PKS Unit. The time of this research was carried out from June to August 2022. This study used the Completely Randomized Design (CRD) method, the first independent variable is blanching time with three levels, namely 0, 10, and 20 minutes. The second independent variable is the storage time which also consists of three levels, namely 0, 24, and 48 hours. Samples with 20-minute blanching treatment showed the lowest ALB levels of 7.72% and a DOBI value of 2.53.